Geopolítica e a produção do espaço urbano na Amazônia Legal: a dinâmica territorial em Bacabeira/MA - Jansen, Márcio Roberto (2022)
The theme chosen for this research addresses geopolitics and the production of urban spaces questioning the impacts caused by economic investments and their interference in the territorial dynamics of small cities in the Legal Amazon of Maranhense. Considering that geopolitics and its influence on the installation of large enterprises in small Brazilian cities provoke an accelerated process of urbanization, attracting a human migratory contingent in a short time, commonly collapsing the offers of housing, health and education. Using the city of Bacabeira/MA as the object of study of this investigation by the unsuccessful attempt to install the Premium I Refinery between 2009 and 2015. It was defined as the general objective of this scientific research: to analyze the relationship of geopolitics in the territorial development of the city of Bacabeira/MA and the direct surroundings of the area destined to the implementation of the refinery in the period from 2009 to 2015. Theoreticalreferences related to geopolitics, territory and production of urban spaces are related to the exemption. It also discusses the relations of geopolitics applied in the production of urban space in the city of Bacabeira/MA andthe territorial dynamics are nalyzed in the time frame from 2009 to 2015. Therefore, the research was defined as descriptive of basic nature, quantitative-qualitative, bibliographic and field approach. The work was written in 3 chapters: methods and theory, which presents the object of the research, the methodological procedures and the theoretical foundation; development of the research, demonstrating the application of the methodology of data collection and analysis and; results and discussions, with the compiled the data collected. The survey concluded that global socioeconomic and political factors give rise to geopolitical decision-making. They are stimulated by financial agents, controllers of landed capital, large companies, national and regional political agents, the media and actors producing urban space, who act under the territory of small cities, especially in Amazonian areas with overvalued natural resources. They act quickly transforming them to the mold of their needs, overcoming the interests and well-being of impacted populations, discarding them when they lose their financial interest, leaving scars on the environment, in the territory, in communities and in people.